Quantifying How Staining Methods Bias Measurements of Neuron Morphologies - Farhoodi, Roozbeh; Lansdell, Benjamin James; Kording, Konrad Paul (Frontiers in Neuroinformatics, 2019)
The process through which neurons are labeled is a key methodological choice in measuring neuron morphology. However little is known about how this choice may bias measurements. To quantify this bias we compare the extracted morphology of neurons collected from the same rodent species, experimental condition, gender distribution, age distribution, brain region and putative cell type, but obtained with 19 distinct staining methods. We found strong biases on measured features of morphology. These were largest in features related to the coverage of the dendritic tree, e.g. the total dendritic tree length. Understanding measurement biases is crucial for interpreting morphological data.